Simple tests for the diagnosis of childhood obesity: a systematic review and meta‐analysis. (21st September 2016) - Simmonds, M.; Llewellyn, A.; Owen, C. G.; Woolacott, N.
Summary: There is a need to accurately quantify levels of adiposity in order to identify overweight and obesity in children. This systematic review aimed to identify all diagnostic accuracy studies evaluating simple tests for obesity and adiposity, including body mass index (BMI), skin‐fold thickness and waist circumference, compared against high‐quality reference tests. Twenty‐four cohort studies including 25, 807 children were included. BMI had good performance when diagnosing obesity: a sensitivity of 81.9% (95% confidence interval [CI]: 73.0 to 93.8) for a specificity of 96.0% (95% CI: 93.8 to 98.1). It was less effective at diagnosing overweight (sensitivity: 76.3%, 95% CI: 70.2 to 82.4; specificity: 92.1% 95% CI: 90.0 to 94.3). When diagnosing obesity, waist circumference had similar performance (sensitivity: 83.8%; specificity: 96.5%). Skin‐fold thickness had slightly poorer performance (sensitivity: 72.5%; specificity: 93.7%). Few studies considered any other tests. There was no conclusive evidence that any test was generally superior to the others. BMI is a good simple diagnostic test for identifying childhood adiposity. It identifies most genuinely obese and adipose children while misclassifying only a small number as obese. There was no conclusive evidence that any test should be preferred to BMI, and the extra complexity of skin‐fold thickness tests does not appear to improve diagnostic accuracy.